PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN BERBASIS CANVA PADA MATERI EKOSISTEM KELAS 10 DI SMA - via, Novia sari; Abidinsyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Biology learning on the ecosystem topic in Grade X at SMA Negeri 10 Banjarmasin was still dominated by lecture-based instruction and the use of less varied learning media, causing students to be less active and experience difficulties in understanding abstract ecosystem concepts. The use of technology-based learning media is needed to improve the quality of learning. This study aimed to develop a Canva-based instructional video on the ecosystem topic for Grade X Senior High School students and to determine its validity, practicality, and effectiveness. This study employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 35 students of Class X D at SMA Negeri 10 Banjarmasin. Data were collected through observation, interviews, validation sheets completed by material, language, and media experts, teacher and student response questionnaires, and learning achievement tests in the form of pretests and posttests. The data were analyzed quantitatively using descriptive statistics to determine the validity, practicality, and effectiveness of the developed media. The results showed that the developed Canva-based instructional video achieved a validity score of 81.7%, which was categorized as highly valid. The practicality level, based on teacher and student responses, reached 82.7%, which was categorized as highly practical. The effectiveness of the media was indicated by an increase in classical learning mastery from 28.57% on the pretest to 74.28% on the posttest. Therefore, the Canva-based instructional video was considered valid, practical, and effective, making it suitable for use in Biology learning on the ecosystem topic for Grade X Senior High School students.